Employability of Graduates from Top-Tier University Brands in Business and Management: An Exploratory Study of Institutional Strategies and Effective Practices - Iqbal, Jawad; Jamal, Warda Najeeb; Akhtar, Kalsoom; Shaikh, Aliya Ahmad (Pakistan Journal of Humanities and Social Sciences, 2024)
This study investigates the top-tier University brands of Pakistan in the fields of Business and Management, concerning their institutional strategies and practices which frequently enable their graduates to become more employable than the relatively low-tier University brands. For this purpose, an exploratory qualitative inquiry has been opted, and as a part of it, 13 one-on-one semi-structured interviews have been conducted with the curriculum developers, course coordinators, instructors, and trainers working at those top accredited Business and Management institutes. The data collected is then thematically analyzed for the examination of the strategies and practices opted by those institutions, and their execution process. The findings of the thematic analysis posit implications for the low-tier Business and Management Institutes that in order to ensure the maximum employability of their graduates, they need to reflect on their institutional strategies and practices regarding the four main areas: Liaising with the industry employers and experts, building enterprise skills through the development of incubation centers, developing support services, and incorporating effective pedagogical methods & activities in the curriculum. Moreover, the results portray an overall need of conducting a pedagogical review for improvising traditional teaching methods with case-based, simulation-based, and project-based learning of the Business and Management institutes of Pakistan.